2010
DOI: 10.1002/jez.600
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in vivo testosterone manipulation on ovarian morphology, follicular development, and follicle yolk testosterone in the homing pigeon

Abstract: To date, our understanding of the function of testosterone in female reproductive physiology is only marginal although there are indications that testosterone is involved in modulating follicular recruitment, growth, atresia, and ovulation. Studies elevating testosterone in breeding female birds have, in most instances, found detrimental effects, such as delayed clutch initiation or decreased clutch size. In our previous study, testosterone treatment of female homing pigeons delayed clutch initiation without d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…The next day females were measured (tarsus 0.1 mm). and oviducts and ovaries were removed to measure follicles for a concurrent study on ovarian dynamics (Goerlich et al 2010). We retrieved tbe implants except from two testosterone-treated females.…”
Section: Experimental Designmentioning
confidence: 99%
“…The next day females were measured (tarsus 0.1 mm). and oviducts and ovaries were removed to measure follicles for a concurrent study on ovarian dynamics (Goerlich et al 2010). We retrieved tbe implants except from two testosterone-treated females.…”
Section: Experimental Designmentioning
confidence: 99%
“…However, the yolk formation and hormone addition to the yolk is finished by the time of ovulation, as no more yolk can be added to the egg after ovulation. Intriguingly, some studies show that the concentrations of androgens decline significantly already between the time of ovulation and oviposition 5 , 6 and one study showed an increase in progesterone between pre- and post-ovulatory follicles 7 . However, the cause and consequence of this different pattern of change among different classes of steroids are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In homing pigeons, as well as in our rock pigeon colony, the second egg is laid on average 44 h after the first egg (Levi ; Goerlich et al. ), and the two chicks usually have 24–36 h difference in hatching time (Johnston and Janiga ; B.‐Y. Hsu, pers.…”
Section: Introductionmentioning
confidence: 99%
“…Rock Pigeons typically lay two eggs as a clutch and the second egg contains much higher testosterone levels than the first egg when fed ad libitum (Goerlich et al 2009). In homing pigeons, as well as in our rock pigeon colony, the second egg is laid on average 44 h after the first egg (Levi 1998;Goerlich et al 2010), and the two chicks usually have 24-36 h difference in hatching time (Johnston and Janiga 1995;B.-Y. Hsu, pers.…”
Section: Introductionmentioning
confidence: 99%